Exogenous strigolactone interacts with abscisic acid-mediated accumulation of anthocyanins in grapevine berries - Ferrero, Manuela; Pagliarani, Chiara; Novák, Ondrej; Ferrandino, Alessandra; Cardinale, Francesca; Visentin, Ivan; Schubert, Andrea (Journal of experimental botany, 2018)
Besides signalling to soil organisms, strigolactones (SLs) control above- and below-ground morphology, in particular shoot branching. Furthermore, SLs interact with stress responses, possibly thanks to a crosstalk with the abscisic acid (ABA) signal. In grapevine (Vitis vinifera L.), ABA drives the accumulation of anthocyanins over the ripening season. In this study, we investigated the effects of treatment with a synthetic strigolactone analogue, GR24, on anthocyanin accumulation in grape berries, in the presence or absence of exogenous ABA treatment. Experiments were performed both on severed, incubated berries, and on berries attached to the vine. Furthermore, we analysed the corresponding transcript concentrations of genes involved in anthocyanin biosynthesis, and in ABA biosynthesis, metabolism, and membrane transport. During the experiment time courses, berries showed the expected increase in soluble sugars and anthocyanins. GR24 treatment had no or little effect on anthocyanin accumulation, or on gene expression levels. Exogenous ABA treatment activated soluble sugar and anthocyanin accumulation, and enhanced expression of anthocyanin and ABA biosynthetic genes, and that of genes involved in ABA hydroxylation and membrane transport. Co-treatment of GR24 with ABA delayed anthocyanin accumulation, decreased expression of anthocyanin biosynthetic genes, and negatively affected ABA concentration. GR24 also enhanced the ABA-induced activation of ABA hydroxylase genes, while it down-regulated the ABA-induced activation of ABA transport genes. Our results show that GR24 affects the ABA-induced activation of anthocyanin biosynthesis in this non-climacteric fruit. We discuss possible mechanisms underlying this effect, and the potential role of SLs in ripening of non-ABA-treated berries.
Keywords: Fruit; Vitis; laktony; Abscisic Acid; ovoce; anthokyaniny; regulátory růstu rostlin; Lactones; Anthocyanins; Plant Growth Regulators; kyselina abscisová